Self-employment among Italian female graduates - Luisa Rosti; Francesco Chelli (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
We investigate gender differences among Italian self employed graduates focusing on flow data from a ten-year labor market transition matrix (1993-2003). Our data show that tertiary education increases the share of self employment in total employment for male workers but reduces the share for female workers. We argue that the disappointment provoked by the gender wage gap in paid employment may induce some female graduates with low entrepreneurial ability to set up on their own, but once in self employment they have lower survival rates than both men in self employment and women in paid employment. Applying Markovian analysis to labor market transitions we confirm our hypothesis: female graduates rarely move from paid employment to self employment, but the reverse is often the case. Thus, what we observe overall, is that education reduces the percentage of women in self employment, and increases the percentage of women in paid employment.
Keywords: 330; Absolventen; Arbeitsmarktintegration; Weibliche Arbeitskräfte; Selbstständige; Zeitreihenanalyse; Italien